2013
DOI: 10.1364/boe.5.000106
|View full text |Cite
|
Sign up to set email alerts
|

Motion artifact and speckle noise reduction in polarization sensitive optical coherence tomography by retinal tracking

Abstract: We present a novel polarization sensitive optical coherence tomography (PS-OCT) system with an integrated retinal tracker. The tracking operates at up to 60 Hz, correcting PS-OCT scanning positions during the acquisition to avoid artifacts caused by eye motion. To demonstrate the practical performance of the system, we imaged several healthy volunteers and patients with AMD both with B-scan repetitions for frame averaging and with 3D raster scans. Under large retinal motions with up to 1 mm amplitude at 0.5 ~a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…However, fibrotic tissue shows form birefringence and can therefore be identified by PS-OCT [123,124]. A recent study using a PS-OCT system with an integrated retinal tracker [125] -which is important since the fixation capability of affected patients is usually poor, leading to heavy motion artifacts -demonstrated that fibrotic lesions can be readily identified and in the majority of cases also segmented by their characteristic birefringence patterns, showing column-like axis orientation patterns in PS-OCT B-scans (cf. Figure 18) [126].…”
Section: Imaging Of Macular Lesionsmentioning
confidence: 99%
“…However, fibrotic tissue shows form birefringence and can therefore be identified by PS-OCT [123,124]. A recent study using a PS-OCT system with an integrated retinal tracker [125] -which is important since the fixation capability of affected patients is usually poor, leading to heavy motion artifacts -demonstrated that fibrotic lesions can be readily identified and in the majority of cases also segmented by their characteristic birefringence patterns, showing column-like axis orientation patterns in PS-OCT B-scans (cf. Figure 18) [126].…”
Section: Imaging Of Macular Lesionsmentioning
confidence: 99%
“…Sugita et al (2014) took advantage of line-scanning laser ophthalmoscope (LSLO) for eye motion artifact correction and speckle noise reduction of polarization sensitive optical coherence tomography (PS-OCT). From its first demonstration for measurements in biological samples (Hee et al (1992)), PS-OCT has become one of the most important tools among the functional extensions of OCT that can assess more than the basic tomographic images of the reflected light intensity (Pircher et al (2006b), Yamanari et al (2008), Yasuno et al (2010)).…”
Section: Methodsmentioning
confidence: 99%
“…The size of speckles can be kept small by using broadband light sources and optics providing high transverse resolution [46,118]. In image processing, speckle noise can be reduced by image averaging and dedicated algorithms [119,120]. PS-OCT also enables the segmentation of structures based on common polarization properties and the determination of interfaces between different tissue segments based on changing polarization properties.…”
Section: Recent Advances In Ps-oct Technologymentioning
confidence: 99%